ASSESSMENT OF THE STRESSED AND DEFORMED STATE OF TRIBOCONTACT BY CHANGE IN THE AVERAGE POWER OF ACOUSTIC EMISSION - Токарук, Віталій; Мікосянчик, Оксана; Мнацаканов, Рудольф; Хімко, Андрій; Ільїна, Ольга (Problems of Friction and Wear, 2022)
The study evaluated the kinetics of changes in antifriction characteristics, the temperature in contact, and averaged acoustic emission power for triboelements made of 30KhHSA steel and duralumin D16 with a discrete electrospark coating of copper with a density of 55-65%. A decrease in the stress-strain state of the tribocontact was established when the D16 duralumin surface was modified with a discrete electrospark coating of copper. This process’s implementation mechanism consists of the localization of elastic-plastic deformations in a discrete layer characterized by high impact viscosity, higher coefficients of thermal conductivity and thermal diffusivity compared to the base material. The copper coating ensures the stability of the parameter of the average power of the acoustic emission both during the run-in stage and subsequent stage of the regular operation of the triboelements. Modifying duralumin significantly reduces the amplitude and intensity of acoustic emission signals during friction. That shows the dominance of relaxation processes in tribocontact caused by the formation of wear-resistant dissipative structures. Based on the modeling results of the stress-strain state of the studied tribosystems, it was established that the electrospark discrete coating of copper on duralumin D16 caused a decrease in the depth of distribution of the equivalent Mises stresses to 15 μm due to their localization in the formed coating. The localization of equivalent stresses in the near-surface layers of reference sample D16 reaches 30 μm. A clear correlative dependence of the stress-strain state of surface layers in frictional contact on acoustic emission parameters, temperature stress relaxation processes, and physical and mechanical properties of the metal was established. It was defined that precisely due to the choice of coating for electrospark alloying of contact surfaces, it is possible to ensure the formation of secondary structures of a specific type during friction, characterized by high wear resistance.